Potensi Irelevansi Sistem Negara Kesatuan Republik Indonesia (NKRI) dalam Konstelasi Politik Global - Wibowo, Prihandono (Global and Policy Journal of International Relations, 2014)
ABSTRACTMany claims stating that the Unitary State of the Republic of Indonesia (NKRI) is final system. Supporter of this argument suggests that the concept of the nation-state has the final. In fact, if viewed from its historical context, system nation-state only one trend of various systems that run by human. System of city-states, kingdoms, empires, and the caliphate is an example of systems that ever existed and became a trend. This suggests that the nation-state is not absolutely necessary for the human system. In addition, the contemporary trend suggests that the nation-state is increasingly irrelevant. Various regional and transnational cooperation of various actors between states and non-state has taken over some of the traditional role of the nation-state. Existence of EU institutions give the real illustration that regionalism system began to replace the nation-state. Contemporary religious movements also brought the idea to replace the nation-state system. Therefore , it is possible that alternative systems, both of which have roots tradition from the past or an entirely new system, will be able to replace the nation-state system. Therefore , the claim that NKRI is a "final system" and " have the final ", should be reviewed.Keywords: International Politic, nation-state, irrelevant, alternative system.DOI:https://doi.org/10.33005/jgp.v2i01.1982